Parametric optimization applied to design a high-performance vaneless-diffuser for CO2 centrifugal compressor - Gasparin, Elóy [UNESP]; Mattos, Vitor [UNESP]; Saltara, Fabio; Mello, Paulo Eduardo; Dezan, Daniel; Yanagihara, Jurandir; Salviano, Leandro [UNESP] (Taylor & Francis, 2024)
Carbon-dioxide (CO2) centrifugal compressors are machines with high potential of usage in power generation plants and oil industry as it achieves high thermal efficiency in the Brayton cycles and contributes to oil production through the capture and storage of CO2 (CCS) in EOR (Enhanced Oil Recovery) systems. High levels of static pressure at the outlet are desired for EOR applications, which are usually obtained through the insertion of vanes in the diffuser. This work intends to increase vaneless-diffuser static pressure recovery by modifying only its meridional profile, ensuring a broader range of off-design operation when compared to vaned diffusers and attending to the fluctuations of mass flow and rotation expected in EOR practical applications. Therefore, a parametric optimization through surrogate model coupled to CFD was performed with three different objective functions that were submitted to single-optimization through the NSGA-II method: Maximize total-to-total polytropic efficiency, minimize total pressure loss coefficient or maximize static pressure recovery coefficient. Additionally, a sensitivity analysis was conducted using Morris Elementary Effects and SS-ANOVA. The results indicated that the optimized geometries increased the total-to-total polytropic efficiency by 2.9%, reduced the total pressure loss coefficient by 24.0% and increased the static pressure recovery coefficient at the design point by 11.4%, which is discussed in detail after a careful phenomenology assessment. The strategy adopted in the present work through a combination of Sensitivity Analysis, surrogate models and CFD increased the vaneless-diffuser static pressure recovery without the need of inserting vanes in the diffuser, which avoid instabilities in the equipment and would restrict its range of off-design operation.
Keywords: Carbon capture; CO2 centrifugal compresso; optimization; sensitivity analysis; Utilization and Storage; vaneless-diffuser